Understanding students' preferences toward the smart classroom learning environment: Development and validation of an instrument. (July 2018) - MacLeod, Jason; Yang, Harrison Hao; Zhu, Sha; Li, Yanhong
Abstract: This article presents the rationale for developing an instrument and initial evidence of validity and reliability in a higher education context. The 40-item instrument measures students' preferences toward the smart classroom learning environment from eight constructs that are characteristic for this environment, including: Student Negotiation, Inquiry Learning, Reflective Thinking, Ease of Use, Perceived Usefulness, Multiple Sources, Connectedness, and Functional Design. Data was purposely collected from a group of 462 college students enrolled in at least one smart classroom course during the time of this study. The results showed no difference in preferences between genders and concluded that the instrument was a valid and reliable tool for measuring college students' preferences toward a smart classroom learning environment. Highlights: Describes the rationale for instrument development in higher education. Develops 40-item instrument to measure students' preferences towards the smart classroom. Provides initial evidence to conclude highly satisfactory validity and reliability. Discusses implications for renovating existing and transitioning to smart classrooms. Discusses directions for research to increase empirical understanding of smart classrooms.